2017
DOI: 10.3390/su9010154
|View full text |Cite
|
Sign up to set email alerts
|

Land Suitability Assessment for Camelina (Camelina sativa L.) Development in Chile

Abstract: Camelina (Camelina sativa L.) is an oilseed with potential for use as a raw material in second-generation biofuels. Camelina has a seed yield of up to 2380 kg·ha −1 and contains around 45% fatty acids. Selection of a suitable site is critical for production optimization. The objective of this study was to determine Chilean agro-climatic suitability for establishing camelina as a productive alternative. Climate and soil requirements and geographical restraints were evaluated for the species, considering the cli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Currently, interest in the study and cultivation of camelina is shown in Europe, Canada, the United States and other countries of the world [4][5][6][7][8][9][10]. In European countries, the yield of camelina amounts to: 1.9 t/ha in Germany, 2.8 t/ha in France [7].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, interest in the study and cultivation of camelina is shown in Europe, Canada, the United States and other countries of the world [4][5][6][7][8][9][10]. In European countries, the yield of camelina amounts to: 1.9 t/ha in Germany, 2.8 t/ha in France [7].…”
Section: Introductionmentioning
confidence: 99%
“…This species is indeed resistant to both drought and frost stress [16]. It has low nutritional requirements [17][18][19], with subsequent positive effects on the environment highlighted by life cycle assessment (LCA) studies [20,21], and can be grown on poor soils, also in a Mediterranean context [22], even if both seed yield and oil yield show substantial variability, i.e., 1.0-3.0 Mg ha −1 and 30-49% w/w respectively [23]. Finally, camelina, considering the presence of both winter and spring cultivar and the relatively brief life cycle, is suitable for double cropping with small grain cereals, soybean, and sunflower [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Energy from biomass contributes significantly to the national energy balance and since Chile is a major agricultural producer, the dendroenergetic potential is very significant, it is therefore, essential that the country considers dendroenergy in its energy strategy and stimulates policies which promote the energetic use of biomass. Chile's potential area for the establishment of dendroenergy plantations reaches 2.05 million hectares [9,11,12]. In addition, there are at least 3 million hectares of eroded soil in the country that can be forested, along with significant areas of manageable native forests, of which approximately half have no other viable use than to generate energy, given their poor quality because of rotting.…”
Section: Opinionmentioning
confidence: 99%
“…In addition, there are at least 3 million hectares of eroded soil in the country that can be forested, along with significant areas of manageable native forests, of which approximately half have no other viable use than to generate energy, given their poor quality because of rotting. The arid north also has over 1 million hectares of land with potential for integration into bioenergy and carbon capture projects [1,[11][12][13].…”
Section: Opinionmentioning
confidence: 99%